Manufacturing method for active material layer for battery, active material layer for battery, and battery
The method addresses the challenge of reducing battery resistance in nonaqueous electrolyte batteries by using a nanosecond pulse laser to create a pathway for electrolyte penetration in the battery active material layer, while maintaining battery capacity.
Patent Information
- Application Number
- JP2023146450
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-08
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-09-08
AI Technical Summary
Existing battery manufacturing methods using nonaqueous electrolyte batteries face challenges in reducing battery resistance while maintaining battery capacity, as conventional methods can lead to a reduction in active material and poor electrolyte permeability.
A method for manufacturing a battery active material layer involves preparing a layer with a binder and active material, and then applying a nanosecond pulse laser with controlled heat input to melt and aggregate the binder, creating a pathway for electrolyte penetration and reducing battery resistance without removing active material.
The method effectively reduces battery resistance by enhancing electrolyte permeability while preventing the loss of active material, thus maintaining battery capacity.
Smart Images

Figure 2025039384000002 
Figure 2025039384000003 
Figure 2025039384000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a method for producing an active material layer for a battery, an active material layer for a battery, and a battery. [Background technology]
[0002] 2. Description of the Related Art Conventionally, in liquid batteries using an electrolyte solution, an active material layer containing a binder and an active material has been used.
[0003] For example, Patent Document 1 discloses a nonaqueous electrolyte battery comprising an electrode group, an exterior material, and a nonaqueous electrolyte, the electrode group comprising a positive electrode, a negative electrode, and a separator, the positive electrode having a positive electrode current collector, and a positive electrode layer containing a positive electrode active material and a binder and formed on the positive electrode current collector, the negative electrode having a negative electrode current collector, and a negative electrode layer containing a negative electrode active material and a binder and formed on the negative electrode current collector, the separator being interposed between the positive electrode layer and the negative electrode layer and wound together with the positive electrode and the negative electrode, at least one of the positive electrode layer and the negative electrode layer being formed on its surface side so as to connect both long sides (S), having less binder than the surface side of the other region (R), and having a plurality of permeation promoting portions that promote permeation of the nonaqueous electrolyte from the surface side of the region (R). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2011-171020 A Summary of the Invention [Problem to be solved by the invention]
[0005] Patent Document 1 discloses a method for forming an area with less binder on the surface of an electrode layer of a battery using a non-aqueous electrolyte by using a CW laser. However, the active material is removed from the electrode layer by the laser irradiation, and the amount of the active material is reduced, which results in a decrease in the battery capacity.
[0006] In addition, the permeability of an electrolyte into an active material layer of a battery affects the resistance of the battery, and therefore it is desirable to reduce the resistance of the battery by improving the permeability of the electrolyte into the active material layer.
[0007] The present disclosure has been made in consideration of the above circumstances, and aims to provide a method for manufacturing an active material layer for a battery, which can reduce the resistance of a battery while suppressing a reduction in battery capacity, an active material layer for a battery, and a battery having the active material layer for a battery. [Means for solving the problem]
[0008] Means for solving the above problems include the following aspects. <1> providing an active material layer including a binder and an active material; A nanosecond pulse laser was applied to the active material layer with a heat dose of 0.005 J / mm 2 More than 0.050J / mm 2 and an irradiation step of irradiating under the following conditions: <2> The irradiation step is a step of irradiating a nanosecond pulse laser under the conditions of an output of 1.25 W or more and 5 W or less and an overlap rate of 0% or more and 63% or less. <1> 2. A method for producing the active material layer for a battery according to claim 1 . <3> An active material layer for a battery comprising a binder and an active material, An active material layer for a battery, wherein an average particle size of the binder in a surface image obtained by EPMA mapping after dyeing the binder is larger than an average particle size of the binder in a cross-sectional image at a depth of 20 μm obtained by EPMA mapping. <4> An active material layer for a battery comprising a binder and an active material, An active material layer for a battery, wherein the binder has an average particle size of 30 μm or more in a surface image obtained by EPMA mapping after dyeing the binder. <5> <3> or <4> 2. A battery comprising the active material layer for a battery according to claim 1 as at least one of a positive electrode active material layer and a negative electrode active material layer. Effect of the Invention
[0009] According to the present disclosure, there are provided a method for manufacturing an active material layer for a battery, which can reduce the resistance of a battery while suppressing a reduction in battery capacity, an active material layer for a battery, and a battery having the active material layer for a battery. [Brief description of the drawings]
[0010] [Figure 1] 1 is a graph showing the results of measuring the change in mass (mass loss (%)) of an active material layer before and after irradiation with a nanosecond pulsed laser in Examples and Comparative Examples. [Diagram 2] 1 is a graph showing the results of measuring battery resistance in Examples and Reference Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, an embodiment that is an example of the present disclosure will be described. These descriptions and examples are merely illustrative of the embodiment, and do not limit the scope of the invention. In the present specification, the upper or lower limit of one numerical range may be replaced with the upper or lower limit of another numerical range. In addition, in the present specification, the upper or lower limit of the numerical range may be replaced with a value shown in the examples.
[0012] Each component may contain multiple types of the corresponding substance. When referring to the amount of each component in a composition, if there are multiple substances corresponding to each component in the composition, unless otherwise specified, it means the total amount of those multiple substances present in the composition. The term "process" includes not only independent processes, but also processes that cannot be clearly distinguished from other processes as long as the intended effect of the process is achieved.
[0013] <Method of manufacturing active material layer for battery> A method for producing an active material layer for a battery according to an embodiment of the present disclosure includes a step of preparing an active material layer including a binder and an active material, and applying a nanosecond pulsed laser to the active material layer with a heat amount of 0.005 J / mm 2 More than 0.050J / mm 2 and an irradiation step of irradiating under the following conditions.
[0014] In the method for producing an active material layer for a battery according to an embodiment of the present disclosure, heat is locally applied to the surface of the active material layer by a nanosecond pulse laser, and at that time, 2 The above heat input is applied. Therefore, the binder on the surface of the active material layer is melted and coagulated by the heat. This ensures a reaction surface on the surface of the active material layer and a permeation path for the electrolyte into the active material layer, thereby reducing the resistance in the battery including this active material layer.
[0015] In addition, a nanosecond pulse laser is used as the laser to irradiate the surface of the active material layer, and the input heat amount during irradiation of the nanosecond pulse laser is 0.050 J / mm 2 In other words, the nanosecond pulsed laser locally applies heat to the surface of the active material layer, and the total amount of heat is suppressed. This prevents the active material from being removed from the active material layer by the laser irradiation, and suppresses the mass loss of the active material, thereby suppressing the reduction in the battery capacity of a battery including this active material layer.
[0016] In addition, by using a nanosecond pulsed laser as the laser to be irradiated onto the surface of the active material layer, removal of the binder from the active material layer is suppressed, thereby maintaining the adhesive strength in the active material layer and suppressing the generation of foreign matter from the active material layer.
[0017] Hereinafter, each step of the method for producing an active material layer for a battery according to an embodiment of the present disclosure will be described.
[0018] -Step of preparing active material layer- The method for manufacturing an active material layer for a battery according to an embodiment of the present disclosure includes a step of preparing an active material layer containing a binder and an active material. Note that as the active material layer, either a negative electrode active material layer or a positive electrode active material layer can be used. The negative electrode active material layer and the positive electrode active material layer can be formed by a conventionally known method. For example, it can be formed by applying and drying a solution containing the raw materials of the active material layer.
[0019] Hereinafter, the active material and the binder will be described separately for the negative electrode active material layer and the positive electrode active material layer.
[0020] ·Negative electrode active material layer Examples of the negative electrode active material include graphite-based carbons such as natural graphite, artificial graphite, and amorphous-coated graphite. In the graphite-based carbon, the proportion of graphite is generally 50% by mass or more, preferably 80% by mass or more. Examples of the binder contained in the negative electrode active material include rubbers such as styrene-butadiene copolymer (SBR) and vinyl halide resins such as polyvinylidene fluoride (PVdF). The negative electrode active material layer may further contain other components such as a thickener. Examples of the thickener include celluloses such as carboxymethyl cellulose (CMC).
[0021] ·Positive electrode active material layer Examples of the positive electrode active material include lithium nickel cobalt manganese composite oxide (hereinafter sometimes simply referred to as "LNCM"). The simplest LNCM has the following general formula: LiNi x Co y Mn z O2 (where x, y, and z in the formula satisfy 0 < x < 1, 0 < y < 1, 0 < z < 1, and x + y + z = 1). LNCM may contain other additive elements in addition to Li, Ni, Co, and Mn, such as transition metal elements other than Ni, Co, and Mn, and typical metal elements other than Li. LNCM has a layered crystal structure. LNCM may exceed 50% by mass of the entire positive electrode active material, for example, and may account for 80 to 100% by mass. The positive electrode active material may be composed of only LNCM. Other examples of the positive electrode active material include lithium nickel composite oxide, lithium cobalt composite oxide, and lithium nickel manganese composite oxide.
[0022] An example of the binder contained in the positive electrode active material layer is a vinyl halide resin such as polyvinylidene fluoride (PVdF). The positive electrode active material layer may further contain other components, such as a conductive material, etc. Examples of the conductive material include non-graphitizable carbon, easily graphitizable carbon such as carbon black, and graphite.
[0023] -Irradiation process- In the next irradiation step, a nanosecond pulse laser is applied to the active material layer with a heat dose of 0.005 J / mm 2 More than 0.050J / mm 2 Irradiate under the following conditions: The nanosecond pulse laser means a pulse laser having a pulse width of 1 ns or more and 500 ns or less, and preferably has a pulse width of 1 ns or more and 100 ns or less.
[0024] ·Input heat amount The input heat of the nanosecond pulse laser irradiated onto the active material layer in the irradiation process is 0.005 J / mm 2 More than 0.050J / mm 2 The following applies. Input heat amount is 0.005J / mm 2 With this amount of heat input being 0.050 J / mm or more, the binder on the surface of the active material layer is melted and coagulated by heat, and a permeation path for the electrolyte into the active material layer is secured, thereby reducing the resistance in the battery including the active material layer. 2 By making the thickness of the active material layer or less, removal of the active material from the active material layer due to laser irradiation is suppressed, and a reduction in the battery capacity of a battery including the active material layer is suppressed. The lower limit of the input heat is 0.010 J / mm 2 It is preferable that the value is equal to or higher than 0.015 J / mm 2 On the other hand, the upper limit of the input heat amount is preferably 0.040 J / mm2 It is preferable that the value is less than 0.030 J / mm 2 It is more preferable that:
[0025] The amount of heat input from the nanosecond pulse laser can be controlled, for example, by adjusting the power and the wrap rate.
[0026] ·output From the viewpoint of reducing the resistance of the battery while suppressing a reduction in the battery capacity, the output of the nanosecond pulse laser is preferably 1.25 W or more and 5.00 W or less, more preferably 1.50 W or more and 4.50 W or less, and even more preferably 2.00 W or more and 3.50 W or less.
[0027] Wrap Rate The overlap rate when irradiating the nanosecond pulse laser is preferably 0% or more and 63% or less, more preferably 0% or more and 55% or less, and even more preferably 0% or more and 30% or less, from the viewpoint of reducing the resistance of the battery while suppressing a reduction in the battery capacity.
[0028] Here, the overlap rate means the ratio of the area of the region irradiated with the nanosecond pulse laser in an overlapping manner, and is expressed by the following formula. Formula: (area where lasers are overlapping and irradiated) / (area where lasers are overlapping and irradiated)+(area where lasers are not overlapping and irradiated) A nanosecond pulsed laser is a pulsed laser with a pulse width as short as a nanosecond, and the entire area to be irradiated is irradiated with the laser by repeatedly irradiating for a short time while moving the laser irradiation position slightly. The area irradiated with the laser overlaps with the previous irradiation area because the movement of the irradiation position is small during the repeated laser irradiation while moving the irradiation position. For example, if the irradiation is repeated without moving the irradiation position at all, the overlap rate is 100%, and if the irradiation position is moved so as to be out of the area irradiated by one laser irradiation and then the irradiation is repeated, the overlap rate is 0%. The overlap rate can be controlled, for example, by adjusting the moving distance during the repeated laser irradiation.
[0029] <Battery active material layer> -First active material layer- In the present disclosure, an active material layer for a battery according to a first embodiment (simply referred to as a "first active material layer") contains a binder and an active material, and the average particle size of the binder in an image of the surface obtained by EPMA mapping after dyeing the binder is larger than the average particle size of the binder in an image of a cross section at a depth of 20 μm obtained by EPMA mapping.
[0030] The fact that the average particle size [A] of the binder on the surface of the active material layer is larger than the average particle size [B] of the binder on the cross section 20 μm deep from the surface indicates that the binder is aggregated on the surface of the active material layer, which ensures a reaction surface on the surface of the active material layer and a permeation path for the electrolyte into the active material layer, thereby reducing the resistance in the battery including this active material layer.
[0031] The first active material layer can be obtained, for example, by the method for producing an active material layer for a battery according to the embodiment of the present disclosure described above.
[0032] -Second active material layer- In the present disclosure, an active material layer for a battery according to a second embodiment (simply referred to as a "second active material layer") contains a binder and an active material, and the average particle size of the binder in a surface image obtained by EPMA mapping after dyeing the binder is 30 μm or more.
[0033] The fact that the average particle size [A] of the binder on the surface of the active material layer is as large as 30 μm or more means that the binder is aggregated on the surface of the active material layer, which ensures a reaction surface on the surface of the active material layer and a permeation path for the electrolyte into the active material layer, thereby reducing the resistance in the battery including this active material layer.
[0034] In the second active material layer, the average particle size [A] of the binder on the surface is 30 μm or more, preferably 40 μm or more, and more preferably 45 μm or more. The upper limit of the average particle size [A] of the binder is, for example, preferably 100 μm or less, and more preferably 70 μm or less.
[0035] The second active material layer can be obtained, for example, by the method for producing an active material layer for a battery according to the embodiment of the present disclosure described above.
[0036] Here, a method for measuring the average particle size [A] of the binder on the surface of the active material layer will be described. First, the active material layer is dyed (e.g., osmium (Os) dyed) according to the binder contained therein. Next, an EPMA (Electron Probe Micro Analysis) mapping image is obtained for the surface of the dyed active material layer. From the obtained mapping image, the top 10% brightness data is calculated, and this brightness data is set as a threshold value to perform binarization processing. From the binarized image, the particle diameter of the binder particles (meaning the length of the longest part in the image of the target binder particle) is measured. This measurement is performed for 20 binder particles, and the arithmetic average value is taken as the average particle diameter. The average particle size [B] of the binder at a cross section 20 μm deep from the surface is measured by exposing the cross section 20 μm deep from the surface by a method such as cutting, and then determining the average particle size in the same manner as the above-mentioned measurement method for the average particle size [A].
[0037] <Battery> The battery according to the embodiment of the present disclosure has the above-mentioned first active material layer or second active material layer as at least one of the positive electrode active material layer and the negative electrode active material layer. The battery includes, for example, a negative electrode, a positive electrode, a separator, and an electrolyte.
[0038] (electrolyte) ·solvent The electrolytic solution contains a solvent (non-aqueous solvent) and an electrolyte. Examples of the solvent (non-aqueous solvent) include N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium bis(fluorosulfonyl)imide (DEME), 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide (EMI), and 1-ethyl-2,3-dimethylimidazolium bis(fluorosulfonyl)imide (DEMI-FSI).
[0039] ·Electrolytes The electrolyte in the electrolytic solution may be, for example, a Li salt, such as lithium bis(fluorosulfonyl)imide (LiFSI), LiPF6 (lithium hexafluorophosphate), lithium tetrafluoroborate (LiBF4), or Li[N(CF3SO2)2]. The amount of the electrolyte may be, for example, 1.0 to 2.0 mol / L, and is preferably 1.0 to 1.5 mol / L.
[0040] The electrolytic solution may contain various additives, such as a thickener, a film-forming agent, a gas generating agent, etc., in addition to the solvent and the electrolyte. The electrolyte is typically a non-aqueous electrolytic solution that is liquid at room temperature (e.g., 25±10°C). The electrolytic solution is typically liquid in the environment in which the battery is used (e.g., a temperature environment of -20 to +60°C).
[0041] (Negative electrode) The negative electrode includes, for example, a negative electrode current collector and a negative electrode active material layer fixed on the negative electrode current collector. The negative electrode current collector is preferably a conductive member made of a metal having good electrical conductivity (e.g., copper). The negative electrode active material layer may be, for example, the first active material layer or the second active material layer described above.
[0042] (positive electrode) The positive electrode includes, for example, a positive electrode current collector and a positive electrode active material layer fixed on the positive electrode current collector. The positive electrode current collector is preferably a conductive member made of a metal having good electrical conductivity (e.g., aluminum). The positive electrode active material layer may be, for example, the first active material layer or the second active material layer described above.
[0043] (Separator) The separator is an electrically insulating porous film. The separator electrically isolates the positive electrode and the negative electrode. The separator may have a thickness of, for example, 5 to 30 μm. The separator may be composed of, for example, a porous polyethylene (PE) film, a porous polypropylene (PP) film, or the like. The separator may have a multi-layer structure. For example, the separator may be composed of a porous PP film, a porous PE film, and a porous PP film laminated in this order. The separator may have a heat-resistant layer on its surface. The heat-resistant layer includes a heat-resistant material. Examples of the heat-resistant material include metal oxide particles such as alumina, and high-melting point resins such as polyimide.
[0044] (Application) Applications of the battery include, for example, power sources for hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), and battery electric vehicles (BEVs). EXAMPLES
[0045] Hereinafter, the present disclosure will be described based on examples, but the present disclosure is not limited to these examples. In the following description, unless otherwise specified, all "parts" and "%" are based on mass.
[0046] <Examples 1 to 4, Comparative Examples 1 to 2> In each of the examples and comparative examples, the active material layer having the composition shown below was irradiated with a laser on the surface of the active material layer while changing the input heat amount by adjusting the output and overlap rate of the nanosecond pulse laser as shown in Table 1. (Irradiation conditions) Laser pulse width: 50ns, output: 2.5W~5W, wrap ratio: 0%~63% Composition of active material layer: negative electrode active material = graphite, binder = styrene butadiene copolymer (SBR), thickener = carboxymethyl cellulose (CMC), conductive material: carbon nanotubes (CNT)
[0047] [Table 1]
[0048] <Evaluation> (1) Mass loss In each of the Examples and Comparative Examples, the change in mass (mass loss (%)) of the active material layer was measured before and after irradiation with the nanosecond pulsed laser. The results are shown in a graph in FIG.
[0049] As shown in the graph in FIG. 1, in Example 1 (input heat amount 0.005 J / mm 2 ), Example 2 (0.01 J / mm 2 ), Example 3 (0.022 J / mm 2 ), and Example 4 (and 0.04 J / mm 2 ), the mass loss of the active material layer was suppressed to 6% or less, whereas in Comparative Example 1 (input heat amount 0.06 J / mm 2 ) and Comparative Example 2 (0.08 J / mm 2 ), the mass loss of the active material layer significantly exceeded 6%.
[0050] (2) Battery resistance Batteries were fabricated using the active material layers of Examples 1 and 2, which had little mass loss, and a battery resistance test was performed. In addition, as a reference example (Reference: Ref), a battery resistance test was also performed on an active material layer whose surface was not irradiated with a nanosecond pulsed laser. The evaluation results are shown in a graph in Figure 2 as a ratio (%) to the reference example (Ref). The battery configuration in the battery resistance test was a lamicelle type (positive electrode 45 mm x 47 mm, negative electrode 47 mm x 49 mm).
[0051] As shown in the graph of FIG. 2, it is understood that in Examples 1 and 2, the battery resistance can be reduced compared to the reference example (Ref).
[0052] (3) Average particle size of binder For Example 1 and the above-mentioned Reference Example (Reference: Ref), the average particle size of the binder was measured in a surface image obtained by EPMA mapping after dyeing the binder. The active material layers of Example 1 and Reference Example were stained with osmium (Os), and EPMA (Electron Probe Micro Analysis) mapping images were obtained for the stained active material layer surfaces. The top 10% brightness data was calculated from the mapping images, and binarization processing was performed by setting this brightness data as a threshold value. From the binarized images, the particle diameter (longest length) of the binder (SBR) particles was measured for 20 binder particles, and the arithmetic average value was taken as the average particle diameter. The results are shown below. -Average particle size- Example 1: 35 μm Reference example (Ref): 17μm
Claims
1. providing an active material layer including a binder and an active material; A nanosecond pulse laser was applied to the active material layer with a heat quantity of 0.005 J / mm 2 0.050J / mm or more 2 and an irradiation step of irradiating under the following conditions:
2. 2 . The method for producing an active material layer for a battery according to claim 1 , wherein the irradiation step is a step of irradiating with a nanosecond pulse laser under conditions of an output of 1.25 W or more and 5 W or less and an overlap ratio of 0% or more and 63% or less.
3. An active material layer for a battery comprising a binder and an active material, An active material layer for a battery, wherein an average particle size of the binder in a surface image obtained by EPMA mapping after dyeing the binder is larger than an average particle size of the binder in a cross-sectional image at a depth of 20 μm obtained by EPMA mapping.
4. An active material layer for a battery comprising a binder and an active material, An active material layer for a battery, wherein the binder has an average particle size of 30 μm or more in a surface image obtained by EPMA mapping after dyeing the binder.
5. A battery comprising the active material layer for a battery according to claim 3 or 4 as at least one of a positive electrode active material layer and a negative electrode active material layer.
Citation Information
Patent Citations
Method for laser micro cladding preparation of hydrogen storage layer of hydrogen evolution electrode
CN105200421A
Power battery pole piece and preparation method thereof
CN114203947A
Nonaqueous secondary battery and method for producing the same
JP2009206079A
Non-aqueous electrolyte secondary battery and manufacturing method of non-aqueous electrolyte secondary battery
JP2020035682A
Electrode for secondary battery, manufacturing method thereof, and secondary battery including the same
JP2021523520A